Effect of elevated CO2 concentration on photosynthetic characteristics of hyperaccumulator Sedum alfredii under cadmium stress. Issue 7 (29th January 2015) - Li, Tingqiang; Tao, Qi; Di, Zhenzhen; Lu, Fan; Yang, Xiaoe
Abstract The combined effects of elevated CO2 and cadmium (Cd) on photosynthetic rate, chlorophyll fluorescence and Cd accumulation in hyperaccumulator Sedum alfredii Hance were investigated to predict plant growth under Cd stress with rising atmospheric CO2 concentration. Both pot and hydroponic experiments were conducted and the plants were grown under ambient (350 µL L−1) or elevated (800 µL L−1) CO2. Elevated CO2 significantly (P < 0.05) increased Pn (105%–149%), Pnmax (38.8%–63.0%) and AQY (20.0%–34.8%) of S. alfredii in all the Cd treatments, but reduced chlorophyll concentration, dark respiration and photorespiration. After 10 days growth in medium with 50 µM Cd under elevated CO2, PSII activities were significantly enhanced (P < 0.05) with Pm, Fv/Fm, Φ(II) and qP increased by 66.1%, 7.5%, 19.5% and 16.4%, respectively, as compared with ambient‐grown plants. Total Cd uptake in shoot of S. alfredii grown under elevated CO2 was increased by 44.1%–48.5%, which was positively correlated with the increase in Pn. These results indicate that elevated CO2 promoted the growth of S. alfredii due to increased photosynthetic carbon uptake rate and photosynthetic light‐use efficiency, and showed great potential to improve the phytoextraction of Cd by S. alfredii.